Tinjauan Yuridis Surat Edaran Mahkamah Agung Nomor 07 Tahun 2014 Ditinjau dari Putusan Mahkamah Konstitusi Nomor 34/Puu-Xi/2013 (International Forum of Researchers and Lecturers, 2024)
The Indonesian Constitutional Court in its judicial review of the Criminal Procedure Code No. 34/PUU-XI/2013 stated that Article 268 paragraph (3) regarding the limit on filing for judicial review of criminal cases is contrary to the 1945 Constitution and has no binding legal force. The Supreme Court responded to the decision by issuing Supreme Court Circular Letter No. 07/2014 which continues to limit judicial review to only one time based on the Judicial Power Act and the Supreme Court Act. Departing from regulatory dualism, this paper formulates the problem of the legal products issued by the Supreme Court and the Constitutional Court in terms of material testing of Law Number 8 of 1981 concerning the Criminal Procedure Code. This study uses normative legal research methods through a review of literature sources. Through Gustav Radbruch's Legal Theory, this study found that first, the position of the SEMA was issued even though it was in accordance with existing laws and regulations, but this decision was contrary to Gustav Radbruch's Legal Theory. Second, the legal consequences after the Constitutional Court Decision. The Supreme Court through SEMA that limits the filing of judicial review to one time is legally flawed both in terms of substance and formal formation because it contradicts the Constitutional Court Decision.